Emerging technologies to extract high added value compounds from fruit residues: sub/supercritical, ultrasound-, and enzyme-assisted extractions - Alexandre, Elisabete M. C. (2019)
Food waste is a growing problem for the food industry, leading to an increase of pollution and economic problems. Fruits and vegetables are very rich in bioactive compounds having many benefits for humans. These biocompounds can be found not only in the fruit/vegetable itself but also in its wastes, after processing. Nonetheless, the conventional extraction methods are highly problematic, due to solvent consumption, long extraction time, and low extraction yields, making it necessary to develop new extraction techniques. In this review, we aim to review the most recent literature on the extraction of bioactive compounds from fruit peels and seeds, using sub/supercritical fluids, ultrasound, and enzymes.